Bifunctional molecules targeting SARS-CoV-2 spike and the polymeric Ig receptor display neutralization activity and mucosal enrichment. Issue 1 (1st January 2021) - White, Ian; Tamot, Ninkka; Doddareddy, Rajitha; Ho, Jason; Jiao, Qun; Harvilla, Paul B.; Yang, Tong-Yuan; Geist, Brian; Borrok, M. Jack; Truppo, Matthew D.; Ganesan, Rajkumar; Chowdhury, Partha; et al.
ABSTRACT: The global health crisis and economic tolls of COVID-19 necessitate a panoply of strategies to treat SARS-CoV-2 infection. To date, few treatment options exist, although neutralizing antibodies against the spike glycoprotein have proven to be effective. Because infection is initiated at the mucosa and propagates mainly at this site throughout the course of the disease, blocking the virus at the mucosal milieu should be effective. However, administration of biologics to the mucosa presents a substantial challenge. Here, we describe bifunctional molecules combining single-domain variable regions that bind to the polymeric Ig receptor (pIgR) and to the SARS-CoV-2 spike protein via addition of the ACE2 extracellular domain (ECD). The hypothesis behind this design is that pIgR will transport the molecule from the circulation to the mucosal surface where the ACE ECD would act as a decoy receptor for the nCoV2. The bifunctional molecules bind SARS-Cov-2 spike glycoprotein in vitro and efficiently transcytose across the lung epithelium in human tissue-based analyses. Designs featuring ACE2 tethered to the C-terminus of the Fc do not induce antibody-dependent cytotoxicity against pIgR-expressing cells. These molecules thus represent a potential therapeutic modality for systemic administration of neutralizing anti-SARS-CoV-2 molecules to the mucosa.